2022
DOI: 10.1111/tid.13835
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 in vaccinated versus unvaccinated hematologic malignancy patients

Abstract: The effect of vaccination on severity of subsequent COVID‐19 in patients with hematologic malignancies (HM) is unknown. In this single‐center retrospective cohort study, we found no difference in severity of COVID‐19 disease in vaccinated (n = 16) versus unvaccinated (n = 54) HM patients using an adjusted multiple logistic regression model. Recent anti‐B‐cell therapy was associated with more severe illness. This article is protected by copyright. All rights reserved

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 24 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…Although clearly important in determining outcomes, antiviral therapies have neither been mentioned nor accounted for in majority of studies examining outcomes following breakthrough infections, which further makes inference difficult from these reports. [5][6][7] In conclusion, patients with HM have a lower response to COVID-19 vaccine, higher rates of breakthrough infections, and subsequently worse outcomes than patients with solid malignancy. Compared to noncancer patients, the vaccine effectiveness against symptomatic infections seems lower in patients with HM visiting academic centers (cumulative infection risk: 4.9% vs. 14.9%) 7 ; however, epidemiological studies are still needed to understand the effectiveness of mRNA vaccination, especially boosters, against COVID-19 severity in this group.…”
Section: Covid-19 Vaccine Effectiveness In Patients With Hematologic ...mentioning
confidence: 92%
See 3 more Smart Citations
“…Although clearly important in determining outcomes, antiviral therapies have neither been mentioned nor accounted for in majority of studies examining outcomes following breakthrough infections, which further makes inference difficult from these reports. [5][6][7] In conclusion, patients with HM have a lower response to COVID-19 vaccine, higher rates of breakthrough infections, and subsequently worse outcomes than patients with solid malignancy. Compared to noncancer patients, the vaccine effectiveness against symptomatic infections seems lower in patients with HM visiting academic centers (cumulative infection risk: 4.9% vs. 14.9%) 7 ; however, epidemiological studies are still needed to understand the effectiveness of mRNA vaccination, especially boosters, against COVID-19 severity in this group.…”
Section: Covid-19 Vaccine Effectiveness In Patients With Hematologic ...mentioning
confidence: 92%
“…DeVoe et al should be commended for including whole-genome sequencing information, albeit for only 16% of the cohort. 5 Also, hospital-or registry-based reports have generally not been able to account for other environmental factors or social determinants of health between vaccinated and unvaccinated groups, all of which could have a direct impact on their COVID-19 exposure, immune response, access to healthcare, clinical trials, and latest anti-COVID therapies, and thus subsequent outcomes. Finally, a persistent theme across studies has been the impact of immunosuppressive agents, that is, anti-B cell therapies, such as anti-CD20 mAb rituximab, on decreasing the vaccine response and increasing COVID-19 severity in HM.…”
Section: Covid-19 Vaccine Effectiveness In Patients With Hematologic ...mentioning
confidence: 99%
See 2 more Smart Citations
“…As a group, those patients are consistently shown to have a high risk of a severe and complicated COVID-19 course with high rates of hospitalization, respiratory failure and death; the risk is particularly elevated in those with B-cell lymphoid malignancies who received lymphocytotoxic therapies. In addition, the humoral vaccine response in this high risk group is blunted and they are less likely to seroconvert after vaccination, although a relatively robust cellular immunity response to vaccine appears to be preserved; however, the data on cellular immunity is still too scarce to allow generalization [ [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] ]. A systematic review that identified 57 studies reporting on 7393 patients reported heterogenous vaccine-induced seroconversion rates and cellular immunity in HM patients, but the response was in general lower than reported in healthy participants in the same studies, with the lowest immunity rates reported in CLL, and the highest in myeloproliferative disorders [ 6 ].…”
Section: Overview Of Covid-19 Risk and Vaccination Benefits In Common...mentioning
confidence: 99%